Protocol for extracellular vesicle secretion-related gene screening via ExoScreen technique - Tomofumi Yamamoto; Fumihiko Urabe; Yusuke Yoshioka; Yusuke Yamamoto; Takahiro Ochiya (STAR Protocols)
Summary: Extracellular vesicles (EVs) play a key role in cancer development and cellular homeostasis by transferring the biological cargo to recipient cells. Here, we describe steps for screening EV secretion-related genes by combining a microRNA (miRNA) library and ExoScreen, a highly sensitive EV detection technique. We also detail procedures for screening the direct target genes regulated by miRNAs. This protocol provides a useful tool for understanding complex intracellular communications involved in EV secretion.For complete details on the use and execution of this protocol, please refer to Yamamoto et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.